Would you say "yes" in the evening? Time-of-day effect on response bias in four types of working memory recognition tasks. (2nd January 2018) - Lewandowska, Koryna; Wachowicz, Barbara; Marek, Tadeusz; Oginska, Halszka; Fafrowicz, Magdalena
ABSTRACT: Across a wide range of tasks, cognitive functioning is affected by circadian fluctuations. In this study, we investigated diurnal variations of working memory performance, taking into account not only hits and errors rates, but also sensitivity ( d ') and response bias ( c ) indexes (established by signal detection theory). Fifty-two healthy volunteers performed four experimental tasks twice – in the morning and in the evening (approximately 1 and 10 h after awakening). All tasks were based on Deese–Roediger–McDermott paradigm version dedicated to study working/short-term memory distortions. Participants were to memorize sets of stimuli characterized by either conceptual or perceptual similarity, and to answer if they recognized subsequent stimulus (probe) as an "old" one (i.e. presented in the preceding memory set). The probe was of three types: positive, negative or related lure. In two verbal tasks, memory sets were characterized by semantic or phonological similarity. In two visual tasks, abstract objects were characterized by a number of overlapping similarities or differed in only one detail. The type of experimental material and the participants' diurnal preference were taken into account. The analysis showed significant effect of time of day on false alarms rate ( F (1, 50)  = 5.29, p  = 0.03, ηp 2  = 0.1) and response bias ( F (1, 50)  = 11.16, p  = 0.002, ηp 2  = 0.18). In other words, in the evening participants responded in more liberal way than in the morning (answering "yes" more often). As the link between variations in false alarms rate, response bias and locus coeruleus activity was indicated in literature before, we believe that our data may be interpreted as supporting the hypothesis that diurnal fluctuations in norepinephrine release have effect on cognitive functioning in terms of decision threshold.